Streamlining and improving controlled drug dispensary workload in a London teaching hospital following the implementation of automated dispensing cabinets on wards: A quality improvement project - Áine Walsh; Emma Jeffrey; Kit Lai (Exploratory Research in Clinical and Social Pharmacy)
An efficiently run pharmacy dispensary has the potential to positively impact patients stay in hospital. Pharmacy dispensary providers work in a fast-paced, hectic environment and are finding it increasingly difficult to keep up with workload demands. In order to meet the increasing demand on resources, pharmacy teams are incorporating Quality Improvement (QI) initiatives to improve efficiencies within systems for the purpose of freeing up nursing and pharmacy staff time, improve patient flow and improve patient safety. This QI project sought to develop a standardised inventory control formula for controlled drugs (CDs) stocked in ADCs in clinical locations in order to reduce the frequency of CD stock orders, minimise the requirement for manual nurse generated orders and in doing so streamline workload for dispensaries whilst ensuring sufficient CD stock holding levels in clinical locations. The introduction of ADCs corresponded with an increase in dispensary workload at the main hospital site at King's College Hospital (KCH). Retrospective time series analysis of the monthly CD dispensing data was analysed for Surgical and Trauma wards over a 27-month period using the Statistical Control Process (SPC) tool. Volume of stock CD dispensing transactions, volume of stock Vs non-stock CD dispensing transactions, volume of weekday vs weekend, morning, afternoon and out of hours CD stock workload were measured. Two interventions were implemented: (i) stock optimisation informed by the utilisation of CD dispensing data issued from the ADC in central pharmacy; (ii) stocklist rationalisation to ensure the most commonly used CDs were added to CD stocklists and the least commonly used CDs were removed from stocklists in addition to the development of a standardised inventory management formula. The main outcome measure was the volume of stock CD dispensing transactions processed by central pharmacy. Secondary outcome measures included the volume of stock CD dispensing transactions at weekends Vs weekdays in addition to the split in workload between mornings, afternoons and out of hours. A reduction in stock CD workload for Surgical and Trauma wards was demonstrated following the stock optimisation review whereas this was not significantly impacted by the stock rationalisation or application of the standardised inventory management formula. Weekend workload reduced by 30 % in comparison to pre-ADC baseline period. Morning, afternoon and out of hours CD stock workload demonstrated a sustained improvement following stock optimisation, stock rationalisation and following the application of the standardised inventory management formula. The only exception to this sustained improvement was in October 2023 following the implementation of a new Trust wide EMPA system. The perfect formula to determine CD stock inventory levels remains elusive, however, as nurses are still required to order stock manually via CD requisition books for stock CD requests. Continual cycles of reviews are made possible through improved ease of data availability with the use of ADCs. Suggestions to further improve the formula are explored although not tested as part of this QI. The proposed improvements to the standardised formula together with more widespread application to different specialties is recommended as the next steps to this QI.